Jordanian nursing students' experience of harassment in clinical care settings - Arwa Masadeh; Rula Al-Rimawi; Aziza Salem; Rami Masa'deh (BMC, 2024)
Abstract Introduction Nursing students experienced various types of bullying and abuse in their practice areas. This study aims to assess the incidence, nature, and types of bullying and harassment experienced by Jordanian nursing students in clinical areas. Methodology A cross-sectional, descriptive design was used, utilizing a self-report questionnaire. A convenient sampling technique was used to approach nursing students who are in their 3rd or 4th year in governmental and private universities. Results Of 162 (70%) students who reported harassment, more than 80% of them were females and single. Almost 40% of them reported that males were the gender of the perpetrator. Almost 26.5% of them reported that patient's relatives or friends were the sources of harassment. Psychological/verbal harassment was the most reported type of harassment (79%). Findings showed that there was a statistically significant difference in psychological/verbal harassment based on gender and type of the university. Also, there were significant negative correlations between psychological/verbal harassment, professional achievement, and personal life. Conclusion Harassment in the clinical area is affecting the professional and personal lives of students, who lack the knowledge of policy to report this harassment.